Standardized risk management in catheterization procedures for non-ST-segment elevation myocardial infarction: associations with in-hospital clinical outcomes. (25th November 2020) - Troestler, J; Parco, C; Brockmeyer, M; Lin, Y; Krieger, T; Quade, J; Bader, S; Kosejian, L; Karathanos, A; Heinen, Y; Schulze, V; Icks, A; et al.
Abstract: Introduction and purpose: Patient risk in non-ST-segment elevation myocardial infarction (NSTEMI) depends on clinical setting, individual patient variables and procedural characteristics. Standardized risk-adjusted periprocedural management for catheterization procedures using a Standard Operating Procedure (SOP) was investigated to evaluate associations with in-hospital clinical outcomes. Methods: In 01/2018, our heart center established an SOP for coronary catheterization procedures in NSTEMI, targeting 1) standardized pre-procedural risk assessment using National Cardiovascular Data Registry (NCDR) risk models, and 2) standardized post-procedural risk-adjusted safety measures, including advanced patient monitoring (intermediate/intensive care) and use of vascular closure devices. All patients presenting with invasively-managed NSTEMI in 2018 were retrospectively evaluated for SOP-based pre-procedural risk scoring, SOP-based post-procedural management and in-hospital clinical outcomes of mortality, major bleeding (MB, according to BARC ≥3) and acute kidney injury (AKI, according to KDIGO). Results: A total of 430 patients (age 72±12 years, 71% male, BMI 27±5) presenting with NSTEMI from 01 to 12/2018 were included, 9.8% presented in cardiogenic shock and 4.7% had suffered a preclinical cardiac arrest. Overall in-hospital mortality was 3.7%, MB occurred in 6.5%. 207 patients (48.1%, SOP+ group) had received both 1) pre-procedural risk assessment and 2) post-procedural risk-adjusted safety measures; the other 223 patients (51.9%, SOP- group) had not received either 1) or 2). There were no significant differences in baseline characteristics and prior-existing medical conditions between groups, however, significantly more patients in SOP- group were treated in emergency settings (39.9% vs. 21.7%, p=0.004). However, significantly more patients in SOP- were treated in emergency settings at higher risk (39.9% (SOP-) vs. 21.7% (SOP+); p<0.001). In univariate analysis, all in-hospital clinical outcomes of mortality (1.4% (SOP+) vs. 5.8% (SOP-); p=0.016), MB (2.9% (SOP+) vs. 9.9% (SOP-); p=0.003) and AKI were significantly lower in the SOP+ group (15.9% (SOP+) vs. 24.2% (SOP-); p=0.033). After correction for the difference in risk between groups due to emergency settings by multivariate logistic regression analysis, MB remained significantly lower in SOP+ (p=0.02), while mortality (p=0.14) and AKI (p=0.19) were not significantly associated with SOP-status anymore. Conclusion: Standardized risk management in invasively managed NSTEMI was associated with significantly lower rates of in-hospital major bleedings. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Junior Clinician Scientist Track, Medical faculty, Heinrich-Heine-University Düsseldorf, Germany